Cell and Gene Therapies: European View on Challenges in Translation and How to Address Them - Rousseau, Cécile F.; Mačiulaitis, Romaldas; Śladowski, Dariusz; Narayanan, Gopalan (Frontiers in Medicine, 2018)
Advanced therapy medicinal products (ATMPs), i.e. cell and gene therapy products, is a rapidly evolving field of therapeutic development. A significant proportion of the products are being developed by academia or Small / Medium enterprises (SMEs). The many challenges in translation posed by this class of products include aspects covering: manufacturing, nonclinical development plan as relevant to clinical trial, marketing authorization and reimbursement. In this context, the term translation refers to the relevance of nonclinical data in relation to how it impacts on appropriate and efficient clinical development. In order to successfully overcome these challenges, a clear understanding of the requirements and expectations of all the stakeholders is critical. This article aims to cover the potential challenges related to such translation and suggested approaches to find solutions based on experience and learnings from the perspective of European Union. While commercial challenges have a significant impact on the ATMPs in general, it is considered outside the scope of this article. However, by adopting a strong scientific basis for translation as suggested in this article, it is likely such an approach would help rather than harm successful real world clinical use of ATMPs.